SITI ZUBAIDAH: THE ISLAMIC FEMINISM REVIEW BASED ON BARLAS’ THEORY - Selly Putri Pratami; Nurhayati Nurhayati; Agus Saripudin (English Review: Journal of English Education, 2021)
This research aims to analyze Islamic feminism in the heroic story of Syair Situ Zubaidah. In this research, it is important to understand that Islamic feminism is based on Islamic religious principles. This research aims to identify the female characters of a literature work and to determine the positions and the role of the characters inside of a family. Then, it is also to determine how the character defends and saves her family and people. The applied method was the qualitative descriptive method. The results showed that the Islamic feminism themes also indicated heroic values. The findings showed the struggles, patience, determination, tawaqal, and istiqomah to deal with life. This research applied the interpretation of Al-Qur'an and Al-Hadith, in the forms of the findings of the previous studies. It was important to do and had to be based on the experts to avoid subjective interpretation.